Analysis of social capital in increasing the income of business actors in the Oebobo traditional market, Kupang City - Humbelina Sintia Putri Tael; Petrus E de Rozari; Chrispy Theresia P Daud; Efandri Agustian (Universitas Nusa Cendana, 2026)
This study aims to analyze the forms, roles, and supporting and constraining factors of social capital in improving the income of business owners at Oebobo Traditional Market, Kupang City. A qualitative descriptive approach was employed using survey methods, with data collected through direct observation and Focus Group Discussions (FGDs) involving traders from the fish, meat, vegetable, and fruit sectors. The analysis focused on three dimensions of social capital: trust, social networks, and social norms. The findings reveal that the market is characterized by survival-oriented social capital, in which long-established trust and strong social solidarity facilitate business continuity. However, social capital remains limited in fostering strategic collaboration, institutional linkages, and market expansion. Rather than substantially increasing income, social capital primarily functions to stabilize cash flow, reduce transaction costs through trusted information exchange, and protect traders' reputations. Long-term trust with suppliers and efficient informal information networks emerged as the main enabling factors, while individualistic competition, weak relationships with government institutions, and the risk of unpaid debts arising from cultural reluctance to enforce payment obligations were identified as major constraints. These findings contribute to the social capital literature by demonstrating that, within traditional market settings, social capital is more effective in sustaining business resilience than in driving income growth or business expansion. They also highlight the need to strengthen institutional networks and collaborative market governance to enhance the economic benefits of social capital. Keywords: Social Capital; Business Income; Oebobo Market; Trust; Networks; Norms